Individual prediction of hemispheric similarity of functional connectivity during normal aging - Zhang, Yingteng (Frontiers in Psychiatry, 2022)
In the aging process of normal people, the functional activity pattern of the brain is in constant change, and the change of the brain runs through the whole life cycle, which plays a crucial role in the track of individual development. In recent years, some studies had been carried out on the brain functional activity pattern during individual aging process from different perspectives, which provides an opportunity for the problem we want to study. In this study, we use the resting-state functional magnetic resonance imaging (rs-fMRI) data from Cambridge Centre for Ageing and Neuroscience (Cam-CAN) database with large sample and long lifespan, and computes the functional connectivity (FC) values for each individual. Based on these values, the hemispheric similarity of functional connectivity (HSFC) obtained by Pearson correlation is used as the starting point of this study. We evaluate the ability of individual recognition of HSFC in the process of aging, as well as the variation trend with aging process. The results show that HSFC can be used to identify individuals effectively, and it can reflect the change rule in the process of aging. In addition, we observe a series of results at the sub-module level and find that the recognition rate in the sub-module is different from each other, as well as the trend with age. Finally, as a validation, we repeat the main results by human brainnetome atlas (BNA) template and without global signal regression, found that has a good robustness. This also provides a new clue to hemispherical change patterns during normal aging.